Ubiquitous and Endoplasmic Reticulum–Located Lysophosphatidyl Acyltransferase, LPAT2, Is Essential for Female but Not Male Gametophyte Development in Arabidopsis - Kim, Hyun Uk (American Society of Plant Biologists, 2005)
Lysophosphatidyl acyltransferase (LPAT) is a pivotal enzyme controlling the metabolic flow of lysophosphatidic acid into different phosphatidic acids in diverse tissues. We examined putative LPAT genes in Arabidopsis thaliana and characterized two related genes that encode the cytoplasmic LPAT. LPAT2 is the lone gene that encodes the ubiquitous and endoplasmic reticulum (ER)–located LPAT. It could functionally complement a bacterial mutant with defective LPAT. LPAT2 and 3 synthesized in recombinant bacteria and yeast possessed in vitro enzyme activity higher on 18:1-CoA than on 16:0-CoA. LPAT2 was expressed ubiquitously in diverse tissues as revealed by RT-PCR, profiling with massively parallel signature sequencing, and promoter-driven β-glucuronidase gene expression. LPAT2 was colocalized with calreticulin in the ER by immunofluorescence microscopy and subcellular fractionation. LPAT3 was expressed predominately but more actively than LPAT2 in pollen. A null allele (lpat2) having a T-DNA inserted into LPAT2 was identified. The heterozygous mutant (LPAT2/lpat2) had minimal altered vegetative phenotype but produced shorter siliques that contained normal seeds and remnants of aborted ovules in a 1:1 ratio. Results from selfing and crossing it with the wild type revealed that lpat2 caused lethality in the female gametophyte but not the male gametophyte, which had the redundant LPAT3. LPAT2-cDNA driven by an LPAT2 promoter functionally complemented lpat2 in transformed heterozygous mutants to produce the lpat2/lpat2 genotype. LPAT3-cDNA driven by the LPAT2 promoter could rescue the lpat2 female gametophytes to allow fertilization to occur but not to full embryo maturation. Two other related genes, putative LPAT4 and 5, were expressed ubiquitously albeit at low levels in diverse organs. When they were expressed in bacteria or yeast, the microbial extract did not contain LPAT activity higher than the endogenous LPAT activity. Whether LPAT4 and 5 encode LPATs remains to be elucidated.